Under-reported relationship: a comparative study of pharmaceutical industry and patient organisation payment disclosures in the UK (2012–2016) - Piotr Ozieranski; Emily Rickard; Shai Mulinari; Marcell Csanádi (BMJ Open)
Objectives To examine the under-reporting of pharmaceutical company payments to patient organisations by donors and recipients.Design Comparative descriptive analysis of payments disclosed on drug company and charity regulator websites.Setting UK.Participants 87 donors (drug companies) and 425 recipients (patient organisations) reporting payments in 2012–2016.Main outcome measures Number and value of payments reported by donors and recipients; differences in reported payments from/to the same donors and recipients; payments reported in either dataset but not the other one; agreement between donor–recipient ties established by payments; overlap between donor and recipient lists and, respectively, industry and patient organisation data.Results Of 87 donors, 63 (72.4%) reported payments but 84 (96.6%) were mentioned by recipients. Although donors listed 425 recipients, only 200 (47.1%) reported payments. The number and value of payments reported by donors were 259.8% and 163.7% greater than those reported by recipients, respectively. The number of donors with matching payment numbers and values in both datasets were 3.4% and 0.0%, respectively; for recipients these figures were 7.8% and 1.9%. There were 24 and 3 donors missing from industry and patient organisation data during the entire study period, representing 38.1% and 3.6% of those in the respective datasets. The share of donor–recipient ties in which industry and patient organisation data agreed about donors and recipients was 38.9% and 68.4% in each dataset, respectively. Of 63 donors reporting payments, only 3 (4.8%) had their recipient lists fully overlapping with patient organisation data. Of 200 recipients reporting industry funding, 102 (51.0%) had their donor lists fully overlapping with industry data.Conclusions Both donors and recipients under-reported payments. Existing donor and recipient disclosure systems cannot manage potential conflicts of interest associated with industry payments. Increased standardisation could limit the under-reporting by each side but only an integrated donor–recipient database could eliminate it.